2014
DOI: 10.1007/s10853-014-8595-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al doping in LaCoO3 on structural, electrical and magnetic properties

Abstract: We report investigations on polycrystalline LaCo 1-x Al x O 3 (x = 0-0.9) bulk samples. The solid state synthesized samples showed a coexistence of rhombohedral and monoclinic phases in the intermediate concentrations (0.2 B x B 0.5) and pure rhombohedral phase otherwise. The observed effect of Al doping on dc transport has been analysed on the basis of small polaron hopping mechanism. The magnetisation results presented give evidence of weak ferromagnetism and anomalous temperature dependence of coercivity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…1), which manifests in the more significant high-energy shoulder in the L 3edge (781.7 eV, Supplementary Fig. 3a, b) as well, as reported previously 20 . In UHV conditions, Zn 2+ and Ni 3+ substitution hardly affects the fraction of Co 3+ HS to LS states.…”
Section: Resultssupporting
confidence: 88%
“…1), which manifests in the more significant high-energy shoulder in the L 3edge (781.7 eV, Supplementary Fig. 3a, b) as well, as reported previously 20 . In UHV conditions, Zn 2+ and Ni 3+ substitution hardly affects the fraction of Co 3+ HS to LS states.…”
Section: Resultssupporting
confidence: 88%
“…synthesized LCO samples can be estimated to be in the range of ≈ 10 5 Ωcm. This is about 3 orders of magnitude higher than the resistivity reported by Aswin et al at the same temperature [10], but in a quite similar range as the values reported by English et al [61] and Jirak et al [63]. Despite the relatively large magnetic Curie-tail shown above (section 3.3.…”
Section: Resistivity Vs Temperature Curvessupporting
confidence: 75%
“…On the one hand, doped and undoped LCO compounds are interesting for applications in hydro-carbon oxidation exhaust catalysis [1][2][3], and in solid oxide fuel cells [4,5]. On the other hand, LCO is regarded a model compound for many cobaltites in terms of the thermally induced magnetic spin state transition, which has triggered a great deal of fundamental research into this compound [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Substituted LaAl perovskites remain rhombohedral also at very high temperature and, in the case of LaCoO3, the rhombohedral structure is also stable above 970 °C [48,49]. In the case of solid solutions intermediate between LaAlO3 and LaCoO3, Aswin et al observed that the rhombohedral phase was accompanied by a secondary monoclinic perovskite phase [50]. No monoclinic phase was observed in our samples.…”
Section: Activity Testsmentioning
confidence: 41%